2007
DOI: 10.1029/2007gl030262
|View full text |Cite
|
Sign up to set email alerts
|

Preferential settling of elongated mineral dust particles in the atmosphere

Abstract: [1] Positions of particles' centers of gravity and folding centers were analyzed for individual dust particles in snow on a high mountain in Japan. Bias of dust particles' centers of gravity was observed: L1 (the longest distance from the center of gravity to the boundary of particles) is 5% (of L1, on average) longer than L2 (1/2 of the longest axis of particles), suggesting that a preferential orientation exists for particles settling heavy side down. Applying that preferential orientation of settling partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…We argue that the lack of a distinct effect due to dust non-spherical particle phase functions on our retrieval (as shown in Fig. 6) appears consistent with the findings by Li and Osada (2007), who showed that only spherical dust particles are persistent downwind of desert regions, because of the preferential settling of elongated dust particles.…”
Section: Discussionsupporting
confidence: 79%
“…We argue that the lack of a distinct effect due to dust non-spherical particle phase functions on our retrieval (as shown in Fig. 6) appears consistent with the findings by Li and Osada (2007), who showed that only spherical dust particles are persistent downwind of desert regions, because of the preferential settling of elongated dust particles.…”
Section: Discussionsupporting
confidence: 79%
“…The only other evidence for the alignment that we have been able to locate comes, indirectly, from analysis of deposited dust, which indicates that particles with high aspect ratios are preferentially removed from dust transported over longer distances (Li and Osada, 2007). In a companion article Li and Osada (2007a) explain the apparently increased settling rates of high aspect ratio particles by invoking vertical alignment, which would lead to reduced viscous drag. The authors then ascribe the alignment to flow shear.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Applying settling velocities from Li and Osada [2007] in the absence of turbulence, giant mode particles would fall the 5 km SABL depth within 12.5 AE 4 h. This explains the loss of giant particles between the fresh and aged profiles (Figure 1c) in all cases, except for flight b604 where giant particles were transported over longer time scales, perhaps due to overnight turbulence in cold-pool outflow. Deposition also plays a role for coarse mode Figure 1.…”
Section: Mechanisms For Size Distribution Changementioning
confidence: 99%